Acceleration and speed performance of Brazilian elite soccer players of different age-categories - Loturco, I.; Jeffreys, I.; Kobal, R.; Cal Abad, C. C.; Ramirez-Campillo, R.; Zanetti, V.; Pereira, L. A.; Nakamura, F. Y. (Journal of Human Kinetics, 2018)
This study aimed to compare vertical jump ability (squat-jump [SJ] and countermovement-jump [CMJ]), relative to body mass mean propulsive power in the jump-squat (MPP-REL JS), and the 0-5, 5-10, and 10-20 m acceleration and speed among soccer players from the same professional club, divided into age-categories (U15 [n = 20], U17 [n = 53], U20 [n = 22] and senior [n = 25] players). The tests were performed at the start of the preseason in indoor facilities. The magnitude-based inference approach and the standardized differences (based on effect sizes) were used to compare the age-groups. The SJ, CMJ, and MPP-REL JS increased across the age-groups up to U20, the latter being similar to senior players. Interestingly, the 0-5 m acceleration was likely and possibly higher in U15 players compared to U17 and senior players. Although soccer athletes improve their unloaded and loaded jump abilities across the age-categories (plateauing during adulthood), the same does not hold true for acceleration capacity, from the early phases of players` development (i.e., U15). Strength and conditioning professionals should seek effective strategies to minimize impairment in maximal acceleration performance of elite soccer players throughout their prospective training programs.